2017
DOI: 10.1136/bjophthalmol-2016-309542
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of retinal status using optical coherence tomography after acute onset endophthalmitis following cataract surgery

Abstract: ERM and ME were the main macular abnormalities diagnosed after 1 year of follow-up, associated with VA less than or equal to 20/40 in 50% of the cases. Ultrastructural abnormalities of the ELM and the ellipsoid band were frequently observed in those patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…ISe disruption has been reported after endophthalmitis in previous studies 14,32 and was noted in 49% of the eyes in our cohort. The presence of ISe disruption was associated with worse visual acuity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…ISe disruption has been reported after endophthalmitis in previous studies 14,32 and was noted in 49% of the eyes in our cohort. The presence of ISe disruption was associated with worse visual acuity.…”
Section: Discussionsupporting
confidence: 77%
“…26 Epimacular membrane and intraretinal cysts had been reported as morphological changes after endophthalmitis. 14,15,17,32 However, these morphological changes were not associated with visual impairment in our case series.…”
Section: Discussioncontrasting
confidence: 48%
“…The term "endophthalmitis maculopathy" was introduced by Morris, Kuhn et al in 1995, 17 but OCT technology has improved our understanding of this concept, highlighting both reversible (edema, epimacular proliferation) and irreversible (atrophic) macular pathology long after endophthalmitis resolution. 26 This is not surprising, as complete vitrectomy frequently reveals pus and inflammatory debris adhering to the surface of the macula (macular hypopyon, Supplementary Video 1). 17 Further studies are needed to better characterize endophthalmitis maculopathy, both anatomically and functionally, with OCT, angiography, microperimetry, and electroretinography.…”
Section: Discussionmentioning
confidence: 94%
“…In this case, the ferroalloy metallic IOFB resulted in retinal thinning, which could have occurred as follows: first, the IOFB could have caused undetected bacterial or viral infection resulting in endophthalmitis, which could have caused retinal and choroidal ischemia, leading to macular atrophy. According to a previous study, macular atrophy was reported in five of 46 patients with endophthalmitis [ 2 ]. Second, direct mechanical damage by an IOFB to the optic disc or adjacent retina could have reduced the retinal thickness and choroidal vasculature.…”
mentioning
confidence: 99%